Analysis of illegal pedestrian crossing behavior on a major divided arterial road. (April 2018) - Shaaban, Khaled; Muley, Deepti; Mohammed, Abdulla
Highlights: This study investigated the pedestrians illegal crossing behavior before, during, and after crossing. Over one-third of all pedestrians crossed in the presence of a vehicle on the road. Most of the pedestrians crossed the road during their first attempt and used the shortest path to cross. Crossing time was affected by gender, age, phone use, type of clothing, crossing in a group, and presence of a vehicle. The presence of a vehicle, as well as other pedestrians and hindrances, altered the illegal crossing behavior of pedestrians. Abstract: Pedestrians' illegal mid-block crossing increases the chances of a crash compared to crossing at marked or signalized crosswalks. Therefore, it is necessary to have an accurate understanding of this type of behavior to be able to prevent it. This paper presents the results from a comprehensive study undertaken to gain insight into illegal pedestrian crossing behavior on a high-speed six-lane divided arterial road that runs through a high-density urban area. Pedestrian behavior data were collected during the different stages of illegal crossing including before crossing, during crossing, and after crossing to determine the effect of hindrances, vehicles, and other pedestrians on the crossing behavior. The results showed that the illegal crossing behavior is mostly undertaken by male pedestrians. Over one-third of all pedestrians crossed in the presence of a vehicle on the road. Out of this group, almost one-third crossed using a rolling gap. The waiting time before crossing was affected by the group size, crossing point (curb or median), and the presence of other pedestrians on the opposite side of the road. Most of the pedestrians crossed the road during their first attempt and used the shortest path to cross. The crossing time was affected by gender, age, mobile phone use, type of clothing, crossing in a group, crossing point, path of crossing, and presence of a vehicle. The decision to cross was based on the presence of vehicles in the middle or far lanes for most pedestrians. Overall, the presence of a vehicle, as well as other pedestrians and hindrances, altered the illegal crossing behavior of pedestrians.